Penyuluhan Pemberian Makanan Pendamping ASI Terhadap Terjadinya Konstipasi Pada Bayi Di Kelurahan Baru Ladang Bambu Kecamatan Medan Tuntungan - Rizky Bakara (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Community service on counseling for complementary feeding of breast milk to prevent constipation in infants in Baru Ladang Bambu Village, Medan Tuntungan District, in 2021 aims to provide education and understanding to mothers of infants in the area about the importance of proper complementary feeding patterns to prevent constipation in infants. Through counseling activities, the community service team conducts socialization on the necessary nutrition for infants during growth phases, balanced strategies for complementary feeding of breast milk, as well as signs and prevention of infant constipation. The counseling methods used include lectures, interactive discussions, and distribution of educational materials to mothers of infants. Evaluation is conducted to measure the understanding and behavioral changes of mothers in providing complementary feeding of breast milk. The results of community service show an increase in knowledge and awareness among mothers about the importance of proper complementary feeding patterns to reduce the risk of infant constipation. This community service is expected to provide significant benefits in improving infant health in Baru Ladang Bambu Village.